DNA Repair Deficiency in Breast Cancer: Opportunities for Immunotherapy. (19th June 2019) - Gilmore, Elaine; McCabe, Nuala; Kennedy, Richard D.; Parkes, Eileen E.
Abstract : Historically the development of anticancer treatments has been focused on their effect on tumor cells alone. However, newer treatments have shifted attention to targets on immune cells, resulting in dramatic responses. The effect of DNA repair deficiency on the microenvironment remains an area of key interest. Moreover, established therapies such as DNA damaging treatments such as chemotherapy and PARP inhibitors further modify the tumor microenvironment. Here we describe DNA repair pathways in breast cancer and activation of innate immune pathways in DNA repair deficiency, in particular, the STING (STimulator of INterferon Genes) pathway. Breast tumors with DNA repair deficiency are associated with upregulation of immune checkpoints including PD-L1 (Programmed Death Ligand-1) and may represent a target population for single agent or combination immunotherapy treatment.